2023
DOI: 10.1186/s12882-023-03060-1
|View full text |Cite|
|
Sign up to set email alerts
|

Unfractionated heparin versus nafamostat mesylate for anticoagulation during continuous kidney replacement therapy: an observational study

Abstract: Background Unfractionated heparin sodium and nafamostat mesylate have long been used as anticoagulants in continuous kidney replacement therapy (CKRT) where citrate is unavailable. This study aimed to determine whether heparin or nafamostat mesylate used during CKRT was associated with a longer filter life. Methods In this single-centre observational study, we included adult patients who required CKRT and used heparin or nafamostat mesylate for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The recommended dosage of nafamostat mesylate indicated in the brochure ranges from 20 to 50 mg/h. However, the dosage pertains to intermittent dialysis [ 12 ], and the optimal dosage for CKRT in critically ill patients remains undetermined [ 13 ]. The literature reports a range of nafamostat dosing.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended dosage of nafamostat mesylate indicated in the brochure ranges from 20 to 50 mg/h. However, the dosage pertains to intermittent dialysis [ 12 ], and the optimal dosage for CKRT in critically ill patients remains undetermined [ 13 ]. The literature reports a range of nafamostat dosing.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Among patients with AKI, sodium citrate anticoagulation resulted in a notably extended filter lifespan in comparison to heparin anticoagulation. 26 , 27 Nafamostat mesylate, a synthetic serine protease inhibitor, 28 is often used in CRRT procedures in Japan and South Korea. 29 , 30 A study has shown that nafamostat mesylate is both safe and effective for critically ill patients undergoing blood purification.…”
Section: Discussionmentioning
confidence: 99%